Dillinama : zahir ~ o ~ batin : outwardly manifest, inwardly hidden - Sayed, Sadia (Gurgaon Shubhi, 2015)
Dillinama : Zahir O Batin Wend through its historic pathways, full of discoveries... a journey through time. These views of Delhi, some fresh, others mellow, surround you with euphoria, whosoever stands across. A shivering branch through the mist, fortress... This 'Delhi' book, with art as its backbone, an anthology of an artist, elliptical, esoteric, woven with her own experiences, put forth just the way she found it, proceeding towards its spiritual core, trying to fathom its mysteries and celebrates its intricate beauty with colour and verve.
Keywords: Monuments in art; Islamic architecture in art; Kings and rulers